Juridical Analysis of State Responsibility in Fulfilling the Rights and Compensation of Fixed-Time Work Agreements (PKWT) Workers in the Outsourcing System - Ade Solahudin; Harmono Harmono (Jurnal Legisci, 2026)
Background. The increasing incidence of more flexible employment relationships, including fixed-term contracts (fixed-time work agreements/PKWT) and outsourced workers, poses new challenges to the protection of workers, including the achievement of employment compensation rights. This has been sufficiently articulated in various laws that are normatively expected to be effective, but in practice, violations of rights still recur. This situation shows a discrepancy between what is ordered and what happens on the ground. Aims. This study seeks to reveal how state responsibility is carried out in fulfilling the rights of PKWT workers, as well as how monitoring and law enforcement are carried out in practice. Methods. This research uses a normative legal approach by examining laws and regulations, legal concepts, and relevant studies, and linking them to emerging practices. Result. The results of the discussion show that the main problem does not lie in the absence of norms, but in how these norms are implemented. Responsibilities in outsourcing systems are not fully distributed, so when a breach occurs, workers are often unsure who is responsible. On the contrary, the functions of supervision and law enforcement have not been properly carried out. Inconsistent supervision and law enforcement responses that tend to be weak mean violations do not result in meaningful consequences for business actors. Under these conditions, the law remains a reference, but it has not fully worked as an effective instrument of protection. As a result, worker protection is still at the formal level and has not been fully felt in practice. Conclusion. Thus, the issue of protecting PKWT workers in the outsourcing system cannot be understood solely as a matter of compliance; it is also related to how the state carries out its supervisory function and ensures clarity of responsibilities in employment relations. Implementation. Without this, the gap between norms and practices will persist, and worker protection will be difficult to fully realize.